2021
DOI: 10.2174/1745017902117010103
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Estimates, Severity, and Risk Factors of Depressive Symptoms among Coronary Artery Disease Patients after Ten Days of Percutaneous Coronary Intervention

Abstract: Background: Depression and cardiovascular disorders are significant determinants of health that affect the quality of life and life expectations. Despite the high importance of depression screening among Coronary Artery Disease (CAD) patients, the time being to assess and treat it remains controversial. Objectives: This study aims to assess the prevalence estimates and severity of depressive symptoms and determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 77 publications
3
9
1
Order By: Relevance
“…Importantly, SCAD-AMI remained as a unique predictor of these psychological states even after controlling for previously identified red flags for poor post-event mental health status, namely female sex, younger age, mental health history, social isolation, socioeconomic disadvantage, diabetes, and nonattendance at CR using logistic regression. 22,23,[25][26][27][28][30][31][32][33] Therefore, the current findings confirm that the emotional difficulty associated with SCAD cannot be attributed simply to the fact that most patients with SCAD are younger females, or to their increased likelihood of having a mental health history. Of note, though, the findings regarding post-SCAD depression were not retained after multivariate adjustment using ANCOVA.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Importantly, SCAD-AMI remained as a unique predictor of these psychological states even after controlling for previously identified red flags for poor post-event mental health status, namely female sex, younger age, mental health history, social isolation, socioeconomic disadvantage, diabetes, and nonattendance at CR using logistic regression. 22,23,[25][26][27][28][30][31][32][33] Therefore, the current findings confirm that the emotional difficulty associated with SCAD cannot be attributed simply to the fact that most patients with SCAD are younger females, or to their increased likelihood of having a mental health history. Of note, though, the findings regarding post-SCAD depression were not retained after multivariate adjustment using ANCOVA.…”
Section: Discussionsupporting
confidence: 78%
“…The findings of the present study suggest that survivors of SCAD-AMI are more likely than their counterparts without SCAD to experience anxiety, depression, distress, and cardiac distress in the 6 mo after their acute event. Importantly, SCAD-AMI remained as a unique predictor of these psychological states even after controlling for previously identified red flags for poor post-event mental health status, namely female sex, younger age, mental health history, social isolation, socioeconomic disadvantage, diabetes, and nonattendance at CR using logistic regression 22,23,25–28,30–33. Therefore, the current findings confirm that the emotional difficulty associated with SCAD cannot be attributed simply to the fact that most patients with SCAD are younger females, or to their increased likelihood of having a mental health history.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The reported incidence of severe depression and anxiety after hospitalization for ACS or heart failure ranges from 10% to 30%, but rises to almost 50% when mild anxiety or depression are included. 6 , 7 , 8 Anxiety and depression have been shown to be an independent risk factor for poorer prognosis in these patients over long term: studies have reported an approximately two-to three-fold increase in major adverse cardiac events over 1–2 years’ follow-up in patients with high anxiety and depression scores. 9 Despite a wealth of available information, the psychological aspects of CVD, as with those of most illnesses, are often ignored by treating clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the diagnosis of CVD may exacerbate anxiety and depressive symptoms in these patients. Some studies have reported a high prevalence of depression among patients with coronary artery disease, with 34% of them experiencing moderate to severe depression, which could negatively affect their prognosis [ 25 ]. A meta-analysis performed by Gathright et al [ 26 ] found that depression was a predictor of all-cause mortality in heart failure.…”
Section: Introductionmentioning
confidence: 99%